Does the Daily Plasma Glucose Variability Impact Maternal Weight Gain in Obese Pregnant Patients With Diabetes? [15M]. (May 2016) - Mehra, Suwan; Gavard, Jeffery A.; Buchanan, Christopher Q.; Goldkamp, Jennifer; Rice, Jim; Artal, Raul
Abstract : INTRODUCTION: To examine the effect of maternal glucose variability on gestational weight gain in obese DM women according to the Institute of Medicine (IOM) guidelines and its impact on adverse maternal and neonatal outcomes. METHODS: This was a retrospective chart review of 161 pregnant women with GDM or T2DM age 18+ from week 28 to delivery. We hypothesized that glucose variability will be a stronger indicator of maternal weight gain and neonatal outcome than any single given blood glucose value. Each patient maintained a daily log of 8 glucose readings (fasting's, pre and post meals and bedtime). The coefficient of variation (standard deviation/mean × 100) was calculated for the entire set of readings. Differences in glucose variability as measured by the coefficient of variation were assessed across all three weight gain groups simultaneously using Analysis of Variance (ANOVA). Pairwise comparisons were made with independent student's t test. RESULTS: There was no significant difference in mean glucose variability across all three weight gain groups simultaneously ( P =.88) for any pairwise comparison. There was no significant difference in mean glucose variability for women and neonates having and not having preeclampsia, large-for-gestational-age (LGA) infants, small-for-gestational-age (SGA) infants, cesarean delivery, or neonatal intensive care unit (NICU) admission. CONCLUSION: Glucose variability does not appear to significantly impact gestational weight gain in obese women with Type 2 diabetes or gestational diabetes or be related to adverse maternal/neonatal outcomes in such women.